EARNING MANAGEMENT TERHADAP NILAI PERUSAHAAN, DENGAN CORPORATE GOVERNANCE SEBAGAI MODERATING VARIABEL DAN FIRM SIZE SEBAGAI VARIABEL KONTROL (STUDI PADA BANK UMUM SWASTA NASIONAL GO PUBLIK DI BURSA EFEK INDONESIA) - AT, Marjani; Puspitosarie, Endah (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
The purpose of this study is to obtain empirical evidence , examine, and explain the: 1. Effect of earnings management on firm value., 2. The influence of corporate governance practices affect both together and partially to the value of the company., 3. The influence of corporate governance practices on the relationship between earnings management and corporate value. The results showed earnings management variables significant positive effect on firm value variable . The contribution of the effect of earnings management variables on firm value , the magnitude of the effect of earnings management on the value of the company amounted to 54.7 %., Variable firm size has a significant positive effect on firm value with a value of 41.3 %., Corporate governance practices consisting of commissioners independent, leadership managerial ownership, institutional ownership, and public accounting classification simultaneously positive and significant effect on firm value with a value of 58.4 %., Corporate governance practices are partially positive and significant effect on firm value is managerial ownership and institutional ownership with respectively 68.6% and 31.6%., Variable earnings management affect firm value is weakened by the presence of institutional ownership. Key words: Earning Management, Â Corporate Governance, Firm Size